Laminated glazing with improved sound insulation properties - Patents.com
Patent Information
- Application Number
- JP2023574344
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-03
- Filing Date
- 2022-05-24
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2042-05-24
AI Technical Summary
There is a need for multilayer interlayer films in laminated glazing panels that provide improved acoustic properties, particularly high attenuation coefficients, while meeting industrial safety requirements and impact resistance.
A laminated glazing comprising a first rigid substrate, a multilayer polymeric interlayer with specific compositions of poly(vinyl acetal) resins and plasticizers, and a second rigid substrate, where the multilayer interlayer has a damping loss coefficient of at least 0.0450 to 0.0850 per square meter, achieved by optimizing the residual hydroxyl and acetate contents and glass transition temperatures of the layers.
The solution achieves enhanced sound insulation properties, as measured by increased attenuation loss coefficients, without compromising impact resistance and mechanical strength, thereby improving the acoustic performance of laminated glazing panels.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001]
[0001] The present disclosure relates to the field of polymer interlayers for insulating glass panels and insulating glass panels having at least one polymer interlayer sheet. In particular, the present disclosure relates to the field of insulating glass panels including polymer interlayers that include multiple thermoplastic layers, having improved acoustic properties, such as improved damping, as measured at a windshield. [Background technology]
[0002]
[0002] Laminated panels are generally panels that are composed of two sheets of substrate (such as, but not limited to, glass, polyester, polyacrylate, or polycarbonate) sandwiched between them with one or more polymer interlayers. Laminated laminated glass panels are commonly utilized in architectural window applications, in automotive and aircraft windows, and in photovoltaic solar panels. The first two applications are generally referred to as laminated safety glass. The primary function of the interlayer in laminated safety glass is to absorb energy from impact or force applied to the glass, to keep the layers of glass bonded together even when force is applied and the glass breaks, and to prevent the glass from breaking into sharp shards. In addition, the interlayer can provide a higher sound insulation rating to the glass, reduce transmission of UV and / or IR light, and increase the aesthetic appeal of the associated window. With respect to solar applications, the primary function of the interlayer is to encapsulate the photovoltaic panels that are used to generate and supply electricity in commercial and residential applications.
[0003]
[0003] It has become common practice to utilize multi-layer or multi-layer interlayers to achieve certain properties and performance characteristics of glass panels. In this specification, the terms "multi-layer" and "multi-layer" refer to interlayers having two or more layers, and multi-layer and multi-layer may be used interchangeably. Multi-layer interlayers typically contain at least one soft layer and at least one hard layer. Interlayers having one soft "core" layer sandwiched between two stiffer or harder "skin" layers have been designed with sound insulation properties of glass panels in mind. Interlayers having the reverse configuration, i.e., one hard layer sandwiched between two softer layers, have been found to improve the impact performance of glass panels and may also be designed with sound insulation in mind. Examples of multi-layer interlayers also include interlayers having at least one "transparent" or uncolored layer, and at least one colored layer or at least one conventional layer, such as a non-acoustic layer, and at least one acoustic layer (i.e., a layer having acoustic properties or the ability to provide sound insulation or reduce sound transmission, as further defined below). Other examples of multi-layer interlayers include interlayers having at least two layers with different colors for aesthetic appeal. The colored layer typically contains a pigment or dye or some combination of pigment and dye.
[0004]
[0004] Interlayer layers are generally produced by mixing a polymeric resin, such as poly(vinyl butyral), with one or more plasticizers and melt processing the mixture into a sheet by any applicable process or method known to those skilled in the art, such as, but not limited to, extrusion. Multilayer interlayers can be produced by processes such as coextrusion or lamination, where the layers are combined together to form a unitary structure. Optionally, other additional components may be added for a variety of other purposes. After the interlayer sheets are formed, they are typically collected and rolled up for transportation and storage and for later use in insulating glass panels, as described below.
[0005]
[0005] The method by which a double-glazed panel is generally manufactured in combination with an interlayer is briefly described below. First, at least one polymer interlayer sheet (single or multi-layer) is placed between two substrates, and any excess interlayer is trimmed from the edge to create an assembly. It is not uncommon to place multiple polymer interlayer sheets or polymer interlayer sheets with multiple layers (or a combination of both) within two substrates to create a double-glazed panel with multiple polymer interlayers. Air is then removed from the assembly by an applicable process or method known to those skilled in the art, for example, via nip rollers, vacuum bags or other degassing mechanisms. In addition, the interlayer is partially pressed to the substrate by any method known to those skilled in the art. In the final step, this pre-bond is made more permanent by high temperature and pressure lamination, or any other method known to those skilled in the art, for example, but not limited to, autoclaving, to form the final integral structure.
[0006]
[0006] Multi-layer interlayers are commercially available, for example, tri-layer interlayers having a soft core layer and two harder skin layers. The hard skin layers provide the handling, processability and mechanical strength of the interlayer; the soft core layer provides acoustic damping properties.
[0007]
[0007] The vibration damping properties of the windshield and side laminate are important to the cabin noise level of a vehicle because the windshield and side laminate occupy a large portion of the cabin area of the vehicle and are the primary path for exterior noise (e.g., wind noise, traffic noise, tire noise, engine noise) to enter the cabin of the vehicle. By having a high vibration damping windshield and side laminate, more of the exterior noise or sound can be absorbed and the cabin remains quieter.
[0008]
[0008] There is a need to maximize the attenuation of a windshield while meeting the industrial safety requirements for the windshield application. The present invention discloses an interlayer that provides the maximum attenuation loss factor needed to provide a safety windshield, as measured directly on the windshield, while also meeting the required impact resistance.
[0009] In summary, it is common to use multilayer interlayers to provide high performance laminates. There is a need in the art for the development of multilayer interlayers that have good optical, mechanical and acoustic characteristics that are desirable in multilayer interlayers. More specifically, there is a need in the art for the development of multilayer interlayers that have good acoustic properties, such as attenuation loss factor, when measured directly on the windshield. Summary of the Invention [Means for solving the problem]
[0010]
[0010] Because of these and other problems in the art, described herein, among other things, is a laminated glazing comprising: a first rigid substrate; a multilayer polymer interlayer; and a second rigid substrate; the multilayer polymer interlayer comprising: a first poly(vinyl acetal) resin having a first residual hydroxyl content and a first residual acetate content, and a first plasticizer, the first poly(vinyl acetal) resin having a glass transition temperature (T g a first layer comprising a second poly(vinyl acetal) resin having a second residual hydroxyl content and a second plasticizer, the second layer having a glass transition temperature (T g a second layer comprising a third poly(vinyl acetal) resin having a third residual hydroxyl content and a third plasticizer, the third layer having a glass transition temperature (T g ), and the second layer is between the first and third layers, and when measured according to procedure 1, the laminated glazing has a glazing area (1 / m2) per glazing area measured directly on the laminated glazing. 2) is a laminated glazing having a damping loss coefficient (η) of at least 0.0450 (0.0500, 0.0550, 0.0600, 0.0650, 0.0700, 0.0750, 0.0800, 0.0850).
[0011] In one embodiment, a windshield comprises: a first glass substrate; a multilayer polymer interlayer; and a second rigid substrate; the multilayer polymer interlayer comprises a first poly(vinyl acetal) resin having a first residual hydroxyl content and a first residual acetate content, and a first plasticizer, and the first poly(vinyl acetal) resin has a glass transition temperature (T) greater than 26° C. g a first layer comprising a second poly(vinyl acetal) resin having a second residual hydroxyl content and a second plasticizer, the second layer having a glass transition temperature (T g a second layer comprising a third poly(vinyl acetal) resin having a third residual hydroxyl content and a third plasticizer, the second layer having a glass transition temperature (T g ), and the second layer is between the first and third layers, and when measured according to Procedure 1, the windshield has a windshield area of (1 / m2) measured directly at the windshield. 2 ) has a damping loss factor (η) of at least 0.0450 (0.0500, 0.0550, 0.0600, 0.0650, 0.0700, 0.0750, 0.0800, 0.0850).
[0012] In an embodiment, the first poly(vinyl acetal) resin and the third poly(vinyl acetal) resin are the same. In an embodiment, the first plasticizer and the third plasticizer are the same. In another embodiment, the second plasticizer is the same as at least one of the first plasticizer or the third plasticizer.
[0013] In an embodiment, the difference between the first residual hydroxyl content and the second residual hydroxyl content is at least 2.0 (2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0) weight percent.
[0014]
[0014] In an embodiment, the multilayer interlayer is a tapered interlayer. In an embodiment, one layer of the multilayer interlayer has a tapered profile, and in another embodiment, all layers of the multilayer interlayer have a tapered profile.
[0015] In an embodiment, the interlayer has a gradient color band, hi an embodiment, the interlayer includes an IR absorber in at least one layer.
[0016] In an embodiment, the interlayer further comprises a non-poly(vinyl acetal) layer.
[0017] In an embodiment, the interlayer has a MIM loss factor (LF) at 20° C. as measured by ISO 16940 of at least 0.29 (0.30, 0.31, 0.32, 0.33, 0.34).
[0018] Also disclosed is a method of making a polymer interlayer as disclosed herein.
[0019] In an embodiment, the laminated glazing is a vehicle windshield, side lite, sunroof or other window. In an embodiment, the laminated glazing is used in a head-up display application.
[0020] In one particular embodiment, the rigid substrate (or substrates) is glass. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 illustrates an example of a vibration response curve to an excitation for measuring a windshield damping loss factor (η) in a first vibration mode. [Diagram 2]
[0022] 13 is a graph showing Windshield Attenuation Loss Factor (η) compared to Laboratory MIM Loss Factor (LF) for Windshield 2. [Diagram 3]
[0023] 1 is a graph showing Windshield Attenuation Loss Factor (η) compared to Laboratory MIM Loss Factor (LF) for Windshield 1. [Figure 4]
[0024] 1 is a graph showing the windshield attenuation loss factor (η) per windshield area (1 / m2) compared to the laboratory MIM loss factor (LF) for both windshields. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022]
[0025] Specifically, described herein is a laminated glazing comprised of a first rigid substrate and a second rigid substrate and a multilayer polymer interlayer. The laminated glazing of the present disclosure has improved acoustic or sound insulation properties as measured by attenuation loss factor. The laminated glazing of the present invention has improved acoustic or sound insulation properties as measured by attenuation loss factor per laminated glazing area (1 / m2) measured directly on the laminated glazing. 2 ) has a damping loss factor (η) of at least 0.0450 (0.0500, 0.0550, 0.0600, 0.0650, 0.0700, 0.0750, 0.0800, 0.0850).
[0023]
[0026] Insulating glass panels comprising the interlayer are also described. The multilayer interlayer of the present invention can be used in insulating glass panel applications, such as safety glass in windshields, side windows, sunroofs, and roof and architectural windows, among other applications.
[0024]
[0027] Each layer of the multilayer polymer interlayer can be made by mixing one or more polymer resins, such as poly(vinyl acetal) resins (e.g., PVB), and one or more plasticizers. A multilayer interlayer generally contains two or more layers and two or more resins of various compositions. For example, poly(vinyl acetal) resins, such as PVB resins, with various residual hydroxyl contents and / or various residual acetate contents are suitable for the layers of the multilayer interlayer composition. In a multilayer that includes two layers, at least one of the two layers is a soft layer and the other layer is a hard layer. In this specification, a "soft layer" or a "softer layer" is a layer that has a glass transition temperature of less than about 20°C. In this specification, a "hard layer" or a "harder layer" generally refers to a layer that is harder or stiffer than another layer and generally has a glass transition temperature at least two degrees (2°C) higher than another layer (e.g., a softer layer).
[0025]
[0028] The multilayer interlayer formed from the composition contains two or more glass transitions, with the lowest glass transition occurring below 20°C, or below 15°C, or below 10°C, or below 5°C, or below 0°C, or below -5°C, or below -10°C.
[0026]
[0029] Conventional multi-layer interlayers, such as three-ply acoustic interlayers, contain a soft core layer composed of a single poly(vinyl butyral) ("PVB") resin with low residual hydroxyl content and high amounts of conventional plasticizers, and two hard skin layers with significantly higher residual hydroxyl content (see, for example, U.S. Pat. Nos. 5,340,654, 5,190,826, and 7,510,771). The residual hydroxyl content and amount of plasticizer in the PVB core resin are optimized so that the interlayer provides optimal acoustic insulation properties under ambient conditions for insulating glass panels, such as windshields and windows installed in vehicles and buildings.
[0027]
[0030] A multi-layer acoustic interlayer, such as a tri-layer, can be designed and manufactured by (1) selecting a plasticizer or mixture of plasticizers, (2) selecting a resin(s) for the skin layer(s) and core layer(s), (3) maintaining a plasticizer balance between the core layer(s) and skin layer(s) (e.g., by selecting a resin with specific properties), and (4) combining the core layer(s) and skin layer(s) to form a multi-layer interlayer by an applicable method, such as coextrusion or lamination. The resulting multi-layer acoustic interlayer provides excellent transparency and sound insulation properties without sacrificing other favorable and desirable features of conventional multi-layer interlayers, such as the optical properties and mechanical strength of glass panels made with the multi-layer acoustic interlayer.
[0028]
[0031] Some terminology and common components found in both general interlayers and the interlayers of the present disclosure and their formation will be described. The terms "polymer interlayer sheet", "interlayer" and "polymer melt sheet" in this specification can generally specify a monolayer sheet or a multilayer interlayer. A "monolayer sheet", as the name implies, is a single polymer layer extruded as one layer. On the other hand, a multilayer interlayer can include multiple layers, such as layers extruded separately, layers extruded together, or any combination of layers extruded separately and layers extruded together. Thus, a multilayer interlayer can include, for example: two or more monolayer sheets combined together ("multilayer sheets"); two or more layers coextruded together ("coextruded sheets"); two or more coextruded sheets combined together; a combination of at least one monolayer sheet and at least one coextruded sheet; a combination of a monolayer sheet and a multilayer sheet; and a combination of at least one multilayer sheet and at least one coextruded sheet. In various embodiments of the present disclosure, the multilayer interlayer includes at least two polymer layers (e.g., monolayer or coextruded and / or laminated together) disposed in direct contact with each other, each layer including a polymer resin as more fully detailed below. As used herein, for multilayer interlayers having at least three layers, "skin layer" generally refers to the outer layer of the interlayer, and "core layer" generally refers to the inner layer(s). Thus, an exemplary embodiment is skin layer / / core layer / / skin layer. In a multilayer interlayer having a skin layer / / core layer / / skin layer configuration, in some embodiments, the skin layer may be harder and the core layer may be softer, and in other embodiments, the skin layer may be softer and the core layer may be harder.
[0029]
[0032] Poly(vinyl acetal) resins are produced by known acetalization processes by reacting polyvinyl alcohol ("PVOH") with one or more aldehydes, such as butyraldehyde, in the presence of an acid catalyst, followed by isolating, stabilizing, and drying the resin. Such acetalization processes are disclosed, for example, in U.S. Pat. Nos. 2,282,057 and 2,282,026, and Wade, B. 2016, Vinyl Acetal Polymers, Encyclopedia of Polymer Science and Technology. 1-22 (online, copyright 2016 John Wiley & Sons, Inc.), the entire disclosures of which are incorporated herein by reference. Resins are commercially available in a variety of forms, for example, Butvar® resins from Solutia Inc., a wholly owned subsidiary of Eastman Chemical Company.
[0030]
[0033] Herein, the residual hydroxyl content of a poly(vinyl acetal) resin (calculated as vinyl alcohol weight percent or PVOH weight percent) refers to the amount of hydroxyl groups remaining on the polymer chain after processing is complete. For example, PVB can be produced by hydrolyzing poly(vinyl acetate) to polyvinyl alcohol (PVOH) and then reacting the PVOH with butyraldehyde. In the process of hydrolyzing polyvinyl acetate, typically not all of the acetate side groups are converted to hydroxyl groups. Furthermore, the reaction with butyraldehyde typically does not result in all of the hydroxyl groups being converted to acetal groups. As a result, in any finished PVB resin, there will typically be residual acetate groups (as vinyl acetate groups) and residual hydroxyl groups (as vinyl hydroxyl groups) as side groups on the polymer chain. Herein, the residual acetate content (calculated as vinyl acetate content percent in poly(vinyl acetal) or poly(vinyl acetate) (PVAc) weight percent) refers to the amount of residual groups remaining on the polymer chain. As used herein, residual hydroxyl content and residual acetate content are measured on a weight percent (wt.%) basis by ASTM D1396.
[0031]
[0034] In embodiments, when the multilayer interlayer of the present invention is three layers, the core layer is a soft layer and the skin layers are hard layers. In other embodiments, the core layer is hard and the skin layers are softer. Other combinations and numbers of layers are possible.
[0032]
[0035] In various embodiments, when the interlayer is a multi-layer interlayer, such as a tri-layer, the flexible (or core) layer comprises a poly(vinyl acetal) resin (or first resin) having from about 7 to about 16 weight percent (wt. %), from about 7 to about 14 wt. %, from about 9 to about 14 wt. %, from about 8.5 to about 12 wt. % of hydroxyl groups, calculated as PVOH %, and for certain embodiments, from about 11 to about 13 wt. % of hydroxyl groups, calculated as PVOH %, although other amounts are possible. The resin may also contain less than 30 wt.% residual acetate groups, less than 25 wt.% residual acetate groups, less than 20 wt.%, less than 15 wt.%, less than 13 wt.%, less than 10 wt.%, less than 7 wt.%, less than 5 wt.%, or less than 1 wt.%, or less than 0.5 wt.%, or from 0 to 30 wt.%, from 1 to 3 wt.%, or from 0 to 30 wt.%, %, 2-25 wt.%, 5-20 wt.%, or 7-15 wt.%, with the remainder being acetal, such as butyraldehyde (which contains an isobutyraldehyde acetal group), optionally with another acetal group, such as a 2-ethylhexanal acetal group, or a mixture of butyraldehyde acetal groups and 2-ethylhexanal acetal groups.
[0033]
[0036] In various embodiments, when the interlayer is a multi-layer interlayer, such as a three-layer, the hard (or skin) layer(s) have a residual hydroxyl content of the resin in the soft (or core) layer that is at least 2 wt.%, or at least 3 wt.%, at least 4 wt.%, at least 5 wt.%, at least 6 wt.%, at least 7 wt.%, at least 8 wt.%, at least 9 wt.%, at least 10 wt.%, at least 11 wt.%, at least 12 wt.%, at least 13 wt.%, at least 14 wt.%, at least 15 wt.%, at least 16 wt.%, at least 17 wt.%, at least 18 wt.%, at least 19 wt.%, at least 20 wt.%, at least 21 wt.%, at least 22 wt.%, at least 23 wt.%, at least 24 wt.%, at least 25 wt.%, at least 26 wt.%, at least 27 wt.%, at least 28 wt.%, at least 29 wt.%, at least 30 wt.%, at least 31 wt.%, at least 32 wt.%, at least 33 wt.%, at least 34 wt.%, at least 35 wt.%, at least 36 wt.%, at least 37 wt.%, at least 38 wt.%, at least 39 wt.%, at least 40 wt.%, at least 41 wt.%, at least 42 wt.%, at least 43 wt.%, at least 44 wt.%, at least 45 wt.%, at least 46 wt.%, at least 47 wt.%, at least 48 wt.%, at least 49 wt.%, at least 50 wt.%, at least 51 wt.%, at least 52 wt.%, at least 53 w %, at least 16 wt.%, at least 17 wt.%, at least 18 wt.%, at least 19 wt.%, or at least 20 wt.%, or more, of residual hydroxyl groups, calculated as % PVOH, and the resin in the skin layer may contain from about 15 to about 35 wt.%, from about 15 to about 30 wt.%, or from about 17 to about 22 wt.%; for certain embodiments, from about 17.25 to about 22.25 wt.%, although other amounts are possible depending on the properties desired.
[0034]
[0037] This difference between poly(vinyl acetal) resins is calculated by subtracting the residual hydroxyl content of the resin with the lower residual hydroxyl content from the residual hydroxyl content of the resin with the higher residual hydroxyl content. As used herein, the term "weight percent difference" or "the difference is at least... weight percent" refers to the difference between two given weight percents, calculated by subtracting one number from the other. For example, a poly(vinyl acetal) resin with a residual hydroxyl content of 12 weight percent has a residual hydroxyl content that is 2 weight percent lower than a poly(vinyl acetal) resin with a residual hydroxyl content of 14 weight percent (14 weight percent - 12 weight percent = 2 weight percent). As used herein, the term "varies" can refer to a higher or lower value than another value. One or more other poly(vinyl acetal) layers can also be present in the interlayer and can have residual hydroxyls within the ranges set forth above. In addition, the residual hydroxyl content of the one or more other poly(vinyl acetal) resins may be the same as or different from the residual hydroxyl content of the first poly(vinyl acetal) resin and / or the second poly(vinyl acetal) resin.
[0035]
[0038] In various embodiments, the poly(vinyl acetal) resin for the soft layer or the poly(vinyl acetal) resin for the hard layer(s) can contain less than 30 wt.% residual acetate groups, less than 25 wt.% residual acetate groups, less than 20 wt.%, less than 15 wt.%, less than 13 wt.%, less than 10 wt.%, less than 7 wt.%, less than 5 wt.%, or even less than 1 wt.% residual acetate groups, calculated as poly(vinyl acetate), with the remainder being acetals, such as butyraldehyde (which includes isobutyraldehyde acetal groups), optionally with other acetal groups, such as 2-ethylhexanal acetal groups, or a mixture of butyraldehyde acetal groups and 2-ethylhexanal acetal groups, as described above.
[0036]
[0039] In some embodiments, the first poly(vinyl acetal) resin and the second poly(vinyl acetal) resin can have different residual acetate contents. For example, in some embodiments, the difference between the residual acetate content of the first poly(vinyl acetal) resin and the residual acetate content of the second poly(vinyl acetal) resin can be at least about 2 weight percent, at least about 3 weight percent, at least about 4 weight percent, at least about 5 weight percent, at least about 6 weight percent, at least about 7 weight percent, at least about 8 weight percent, at least about 9 weight percent, at least about 10 weight percent, at least about 12 weight percent, at least about 14 weight percent, at least about 16 weight percent, at least about 18 weight percent, at least about 20 weight percent, at least about 24 weight percent, or at least 29 weight percent. One of the poly(vinyl acetal) resins can have a residual acetate content of about 4 weight percent or less, about 3 weight percent or less, about 2 weight percent or less, or about 1 weight percent or less, measured as described above. In some embodiments, one of the first poly(vinyl acetal) resin and the second poly(vinyl acetal) resin can have a residual acetate content of at least 4 weight percent, at least about 5 weight percent, at least about 6 weight percent, at least about 7 weight percent, about 8 weight percent, at least about 10 weight percent, at least about 12 weight percent, at least about 14 weight percent, at least about 16 weight percent, at least about 18 weight percent, at least about 20 weight percent, at least about 25 weight percent, or at least about 30 weight percent.In other embodiments, the first poly(vinyl acetate) resin and the second poly(vinyl acetate) resin together can have a residual acetate content of at least 4 weight percent, at least about 5 weight percent, at least about 6 weight percent, at least about 7 weight percent, about 8 weight percent, at least about 10 weight percent, at least about 12 weight percent, at least about 14 weight percent, at least about 16 weight percent, at least about 18 weight percent, at least about 20 weight percent. The difference in the residual acetate content between the first poly(vinyl acetal) resin and the second poly(vinyl acetal) resin can be within the ranges described above, or the difference can be less than about 3 weight percent, about 2 weight percent or less, about 1 weight percent or less, or about 0.5 weight percent or less. Additional poly(vinyl acetal) layers present in the interlayer can have the same or different residual acetate content as the residual acetate content of the first poly(vinyl acetal) resin and / or the second poly(vinyl acetal) resin.
[0037]
[0040] The poly(vinyl acetal) resins of the present disclosure, such as one or more poly(vinyl butyral) (PVB) resins, typically have a molecular weight of greater than 50,000 Daltons, or less than 500,000 Daltons, or from about 50,000 to about 500,000 Daltons, or from about 70,000 to about 500,000 Daltons, or from about 100,000 to about 425,000 Daltons, as measured by size exclusion chromatography using a low angle laser light scattering detector, a differential refractometer, or a UV detector. As used herein, the term "molecular weight" refers to weight average molecular weight.
[0038]
[0041] Various adhesion control agents ("ACA") can be used in the interlayers of the present disclosure to control adhesion of the interlayer sheet to glass. In various embodiments of the interlayers of the present disclosure, the interlayers can include about 0.003 to about 0.15 parts by weight of ACA per 100 parts by weight of resin; about 0.01 to about 0.10 parts by weight of ACA per 100 parts by weight of resin; and about 0.01 to about 0.04 parts by weight of ACA per 100 parts by weight of resin. Such ACAs include, but are not limited to, ACAs disclosed in U.S. Pat. No. 5,728,472 (the entire disclosure of which is incorporated herein by reference), sodium acetate, potassium acetate, magnesium bis(2-ethylbutyrate), and / or magnesium bis(2-ethylhexanoate).
[0039]
[0042] Other additives can be incorporated into the interlayer to enhance its performance in the final product and impart certain additional properties to the interlayer. These additives include, but are not limited to, dyes, pigments, stabilizers (e.g., UV stabilizers), antioxidants, antiblocking agents, flame retardants, IR absorbers or IR blockers (e.g., indium tin oxide, antimony tin oxide, lanthanum hexaboride (LaB6) and cesium tungsten oxide), processing aids, flow improvers, lubricants, impact modifiers, nucleating agents, heat stabilizers, UV absorbers, dispersants, surfactants, chelating agents, coupling agents, adhesives, primers, enhancing additives, and fillers, among others known to those skilled in the art.
[0040]
[0043] In various embodiments, the plasticizer may be selected from a high refractive index plasticizer, a mixture of two or more high refractive index plasticizers, or a mixture of a conventional plasticizer and one or more high refractive index plasticizer(s).
[0041]
[0044] Plasticizers having a refractive index of about 1.450 or less are referred to herein as "conventional plasticizers." Conventional plasticizers include, but are not limited to, triethylene glycol di-(2-ethylhexanoate) ("3GEH"), triethylene glycol di-(2-ethylbutyrate), triethylene glycol diheptanoate, tetraethylene glycol diheptanoate, tetraethylene glycol di-(2-ethylhexanoate), dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, di(butoxyethyl) adipate, and bis(2-(2-butoxyethoxy)ethyl) adipate, dibutyl sebacate, dioctyl sebacate, and mixtures thereof. These plasticizers have a refractive index of about 1.442 to about 1.449. In comparison, PVB resins have a refractive index of approximately 1.485 to 1.495. With interlayers produced for a variety of properties and applications, 3GEH (refractive index = 1.442) is one of the most common plasticizers present.
[0042]
[0045] In various embodiments, one or more high refractive index plasticizer(s) may be used. In embodiments, for both the core layer and / or the skin layer, the high refractive index plasticizer(s) are selected such that the refractive index of the plasticizer is at least about 1.460, or is greater than about 1.460, or is greater than about 1.470, or is greater than about 1.480, or is greater than about 1.490, or is greater than about 1.500, or is greater than 1.510, or is greater than 1.520. As used herein, a "high refractive index plasticizer" is a plasticizer having a refractive index of at least about 1.460. In some embodiments, the high refractive index plasticizer(s) is used in conjunction with a conventional plasticizer, and in some embodiments, when included, the conventional plasticizer is triethylene glycol di-(2-ethylhexanoate) ("3GEH"), and the refractive index of the plasticizer mixture is at least 1.460. As used herein, the refractive index of plasticizers or resins used throughout this disclosure is measured according to ASTM D542 at a wavelength of 589 nm and 25° C., or as reported in the literature according to ASTM D542.
[0043]
[0046] Examples of plasticizers having a high refractive index that can be used include, but are not limited to, polyadipates (RI about 1.460 to about 1.485); epoxides (RI about 1.460 to about 1.480); phthalates and terephthalates (RI about 1.480 to about 1.540); benzoates (RI about 1.480 to about 1.550); and other specialty plasticizers (RI about 1.490 to about 1.520). Specific examples of suitable high refractive index plasticizers include, but are not limited to, dipropylene glycol dibenzoate, tripropylene glycol dibenzoate, polypropylene glycol dibenzoate, isodecyl benzoate, 2-ethylhexyl benzoate, diethylene glycol benzoate, propylene glycol dibenzoate, 2,2,4-trimethyl-1,3-pentanediol dibenzoate, 2,2,4-trimethyl-1,3-pentanediol benzoate isobutyrate, 1,3-butanediol dibenzoate, diethylene glycol Included are coal di-o-toluate, triethylene glycol di-o-toluate, dipropylene glycol di-o-toluate, 1,2-octyl dibenzoate, tri-2-ethylhexyl trimellitate, bis-phenol A bis(2-ethylhexanoate), ethoxylated nonylphenol, nonylphenyl tetraethylene glycol, dioctyl phthalate, diisononyl phthalate, di-2-ethylhexyl terephthalate, mixtures of benzoic acid esters of dipropylene glycol and diethylene glycol, and mixtures thereof.
[0044]
[0047] The total plasticizer content in the interlayer may be in the range of 0 to 120 phr, or greater than 0 phr, or greater than 5 phr, or greater than 10 phr, or greater than 15 phr, or greater than 20 phr, or greater than 25 phr, or greater than 30 phr, and / or 120 phr or less, or 115 phr or less, or 110 phr or less, or 105 phr or less, or 100 phr or less, or 95 phr or less, or 90 phr or less, or 85 phr or less, or 80 phr or less, or 75 phr or less, or 70 phr or less, or 10 to 100 phr, or 20 to 80 phr, or 30 to 70 phr. In various embodiments of the interlayer of the present disclosure, the interlayer comprises a total plasticizer of more than 5 phr, about 5 to about 120 phr, about 10 to about 90 phr, about 20 to about 70 phr, about 30 to about 60 phr, or less than 120 phr, or less than 90 phr, or less than 60 phr, or less than 40 phr, or less than 30 phr. Although the total plasticizer content is given above, the plasticizer content of the skin layer(s) or core layer(s) may be different from the total plasticizer content. In addition, as disclosed in U.S. Pat. No. 7,510,771 (the entire disclosure of which is incorporated herein by reference), the plasticizer content of each layer at equilibrium is determined by the residual hydroxyl content of each of the layers, so that the skin layer(s) and core layer(s) can have different plasticizer types and different plasticizer contents within the ranges mentioned above. For example, if the combined skin layer thickness is equal to the core layer thickness, and the total plasticizer content of the interlayer is about 45.4 phr, then at equilibrium the interlayer may contain two skin layers each containing 30 phr of plasticizer and a core layer containing 65 phr of plasticizer. For thicker or thinner skin layers, the total plasticizer content of the interlayer will vary accordingly. When the plasticizer content of an interlayer is given herein, it is determined by reference to the phr of plasticizer in the mixture or melt used to make the interlayer.
[0045]
[0048] The amount of plasticizer in the interlayer depends on the glass transition temperature (T g ) and final acoustic performance. g ) is the temperature that marks the transition of the interlayer from a glassy state to a rubbery state. Generally, a higher amount of plasticizer loading results in a lower T g Conventional interlayers that have been used in the past generally have a T range of about -10 to 25°C for acoustic (noise reduction) interlayers. g , and up to about 45°C T for hurricane and aircraft (more rigid or structural) interlayer applications. g The glass transition temperature (T g ) can be determined by dynamic mechanical thermal analysis (DMTA) in shear mode. DMTA measures the storage (elastic) modulus (G') (in Pascals), loss (viscous) modulus (G'') (in Pascals), and tan delta (=G'' / G') of a specimen as a function of temperature at a given frequency and temperature sweep rate. A frequency of 1 Hz and a temperature sweep rate of 3° C. / min were used herein. T g is determined by the location of the tan delta peak on the temperature scale (° C.), and the tan delta peak value is referred to as tan delta or peak tan delta. In this specification, "tan delta," "peak tan delta," "tan δ," and "peak tan δ" can be used interchangeably.
[0046]
[0049] Glass transition temperature of the interlayer (T g) is also related to the stiffness of the interlayer, and generally, the higher the glass transition temperature, the stiffer the interlayer. Generally, an interlayer having a glass transition temperature of 30° C. or higher increases the windshield mechanical strength and torsional stiffness. On the other hand, a soft layer or interlayer (generally characterized by a layer or interlayer having a glass transition temperature of less than 20° C.) contributes to the sound-reducing effect (i.e., acoustic properties). The interlayer of the present disclosure can have a glass transition temperature of about 26° C. or higher, or about 35° C. or higher for the harder layer(s), and a glass transition temperature of about 20° C. or lower, or 15° C. or lower, or 10° C. or lower, or about 5° C. or lower, or 0° C. or lower, or about -5° C. or lower, or about -10° C. or lower for the soft layer(s), although other glass transition temperatures are possible depending on the desired performance and properties.
[0047]
[0050] In some embodiments, the multilayer interlayers of the present disclosure combine these two advantageous properties (i.e., strength and acoustics) by utilizing harder or stiffer skin layers (e.g., hard / / soft / / hard) laminated with a softer core layer. In various embodiments, the multilayer interlayers generally include a harder layer(s) comprising a poly(vinyl acetal) resin(s) having a glass transition temperature of about 26°C to about 60°C, about 26°C to 40°C, about 26°C or higher, about 30°C or higher, and about 35°C or higher, and a softer layer(s) having a glass transition temperature of about 20°C or lower, about 10°C or lower, or about 5°C or lower, or about 0°C or lower, or about -5°C or lower, or about -10°C or lower.
[0048]
[0051] The final interlayer, whether formed from extrusion or coextrusion or by lamination of multiple layers, generally has a randomly roughened surface topography as formed by melt fracture of the polymer melt as it exits the extrusion die, and further can be embossed on the randomly roughened surface on one or both sides (e.g., a skin layer) by any embossing method known to one of ordinary skill in the art.
[0049]
[0052] While all methods for producing polymer interlayer sheets known to those skilled in the art are considered possible methods for producing the polymer interlayer sheets described herein, this application focuses on polymer interlayer sheets produced by extrusion and coextrusion methods. The final laminated glass panel of the present invention is formed using lamination methods known in the art.
[0050]
[0053] Typically, the thickness or gauge of the polymer interlayer sheet ranges from about 15 mils to about 100 mils (about 0.38 mm to about 2.54 mm), about 15 mils to about 60 mils (about 0.38 mm to about 1.52 mm), about 20 mils to about 50 mils (about 0.51 to about 1.27 mm), and about 15 mils to about 35 mils (about 0.38 to about 0.89 mm). In various embodiments, each of the layers of the multilayer interlayer, such as the skin and core layers, can have a thickness of about 1 mil to about 99 mils (about 0.025 to about 2.51 mm), about 1 mil to about 59 mils (about 0.025 to about 1.50 mm), 1 mil to about 29 mils (about 0.025 to about 0.74 mm), or about 2 mils to about 28 mils (about 0.05 to about 0.71 mm), although other thicknesses may be selected depending on the desired performance and properties.
[0051]
[0054] Many of the embodiments described below refer to a polymer resin that is PVB, however, it will be understood by those skilled in the art that the polymer may be any polymer suitable for use in multi-layer panels. Exemplary polymers include, but are not limited to, polyvinyl acetal (PVA) (e.g., poly(vinyl butyral) (PVB) or poly(vinyl isobutyral), an isomer of poly(vinyl butyral) also referred to as PVisoB, aliphatic polyurethanes (PU), poly(ethylene-co-vinyl acetate) (EVA), polyvinyl chloride (PVC), poly(vinyl chloride-co-methacrylate), polyethylene, polyolefins, ethylene acrylate ester copolymers, poly(ethylene-co-butyl acrylate), silicone elastomers, epoxy resins, and acid copolymers such as ethylene / carboxylic acid copolymers and their ionomers derived from any of the aforementioned possible thermoplastic resins, combinations of the foregoing, and the like. PVB and its isomers polyvinyl isobutyral, polyvinyl chloride, ionomers, and polyurethanes are generally preferred polymers for the interlayer, with PVB (including its isomer PVisoB) being particularly preferred.
[0052]
[0055] Examples of illustrative multi-layer interlayer constructions include, but are not limited to, PVB / / PVisoB / / PVB (PVisoB layers contain two or more resins or different polymer compositions with different residual hydroxyl content and / or different residual acetate content); PVC / / PVB / / PVC, PU / / PVB / / PU, ionomer / / PVB / / ionomer, ionomer / / PU / / ionomer, ionomer / / EVA / / ionomer (core layer PVB (including PVisoB), PU or EVA can contain one resin with one glass transition or two or more resins with different glass transitions). Alternatively, the skin layers and core layers may all use the same or different raw resins, PVB with the same or different residual hydroxyl content and / or residual acetate content, and the same or different plasticizers. Other combinations of resins and polymers will be apparent to those skilled in the art.
[0053]
[0056] Although commonly referred to as poly(vinyl acetal) or poly(vinyl butyral), any poly(vinyl acetal) resin can include the residue of any suitable aldehyde, such as isobutyraldehyde, as previously described. In some embodiments, the one or more poly(vinyl acetal) resins include at least one C1-C 10 The aldehyde may include an aldehyde or a residue of at least one C4-C8 aldehyde. Examples of suitable C4-C8 aldehydes may include, but are not limited to, n-butyraldehyde, isobutyraldehyde, 2-methylvaleraldehyde, n-hexylaldehyde, 2-ethylhexylaldehyde, n-octylaldehyde, and combinations thereof. At least one of the first poly(vinyl acetal) resin and the second poly(vinyl acetal) resin can comprise at least about 20 weight percent, at least about 30 weight percent, at least about 40 weight percent, at least about 50 weight percent, at least about 60 weight percent, or at least about 70 weight percent of residues of at least one C4-C8 aldehyde, based on the total weight of the aldehyde residues of the resin, and / or can comprise up to about 90 weight percent, up to about 85 weight percent, up to about 80 weight percent, up to about 75 weight percent, up to about 70 weight percent, or up to about 65 weight percent of at least one C4-C8 aldehyde, or can comprise in the range of from about 20 to about 90 weight percent, from about 30 to about 80 weight percent, or from about 40 to about 70 weight percent of at least one C4-C8 aldehyde. The C4-C8 aldehyde may be selected from the group listed above, or may be selected from the group consisting of n-butyraldehyde, isobutyraldehyde, 2-ethylhexylaldehyde, and combinations thereof.
[0054]
[0057] In various embodiments, the one or more poly(vinyl acetal) resins can be poly(vinyl butyral) (PVB) resins. In other embodiments, the one or more poly(vinyl acetal) resins can be poly(vinyl butyral) resins that comprise primarily residues of n-butyraldehyde, and can include, for example, about 50 weight percent or less, about 40 weight percent or less, about 30 weight percent or less, about 20 weight percent or less, about 10 weight percent or less, about 5 weight percent or less, or about 2 weight percent or less of residues of aldehydes other than butyraldehyde, based on the total weight of all aldehyde residues of the resin.
[0055]
[0058] As used herein, a multi-layer panel may include a single substrate, such as glass, acrylic, or polycarbonate (or other rigid substrate), with a polymer interlayer sheet disposed thereon, and most commonly a polymer film further disposed over the polymer interlayer. The combination of polymer interlayer sheet and polymer film is generally referred to in the art as a bi-layer. A typical multi-layer panel having a bi-layer structure is (glass) / / (polymer interlayer sheet) / / (polymer film), where the polymer interlayer sheet may include multiple interlayers, as described above. The polymer film serves as a performance-enhancing layer, providing a smooth, thin, rigid substrate that provides better optical qualities than would normally be obtained with a polymer interlayer sheet alone. The polymer film differs from the polymer interlayer sheet used herein in that it does not by itself provide the necessary puncture resistance and glass retention properties, but rather provides performance improvements, such as infrared absorption properties. Poly(ethylene terephthalate) ("PET") is the most commonly used polymer film. Generally, as used herein, a polymer membrane is thinner than a polymer sheet, for example, having a thickness of about 0.001 to 0.2 mm, although other thicknesses may be used.
[0056]
[0059] The interlayers of the present disclosure are most commonly utilized in multi-layer panels that include two substrates, such as a pair of glass sheets (or other rigid materials known in the art, such as polycarbonate or acrylic), and an interlayer disposed between the two substrates. One example of such a structure is (glass) / / (polymer interlayer sheet) / / (glass), where the polymer interlayer sheet can include the multi-layer interlayer described above, as described above. These examples of multi-layer panels are in no way meant to be limiting, and are intended for those skilled in the art to readily recognize that numerous structures other than those described above can be made with the interlayers of the present disclosure.
[0057]
[0060] A typical glass lamination process includes the following steps: (1) assembling two substrates (e.g., glass) and an interlayer; (2) briefly heating the assembly by IR radiation or convection means; (3) passing the assembly through pressure nip rolls for a first degassing; (4) heating the assembly a second time to about 60°C to about 120°C to provide the assembly with sufficient temporary adhesion to seal the interlayer edges; (5) passing the assembly through a second pressure nip roll to further seal the interlayer edges and allow for further handling; and (6) autoclaving the assembly at a temperature of about 135°C to about 150°C and a pressure of about 180 psig to about 200 psig for about 30 to 90 minutes. The actual steps and times and temperatures can be varied as needed, as known to those skilled in the art.
[0058]
[0061] Other means used in degassing the interlayer-glass interface (steps 2-5) known in the art and commercially practiced include the vacuum bag method and the vacuum ring method, which utilize a vacuum to remove air.
[0059]
[0062] The laboratory damping loss factor (LF) was measured by mechanical impedance measurement (MIM) (also called laboratory MIM loss factor) as described in ISO16940. A laminated glass rod specimen, 25 mm wide and 300 mm long, with a pair of 2.3 mm transparent glass, is prepared and excited at the rod's center position by a vibration shaker (Brüel & Kjær). An impedance head (Brüel & Kjær) is used to measure the force exciting the rod to vibrate, and the velocity of vibration, and the resulting transfer function is recorded with a National Instruments data acquisition and analysis system. The loss factor of the first vibration mode is calculated using the half-power method. The laminates are conditioned at room temperature for 4 weeks after lamination and at least 4 hours at the test temperature (e.g. 20 °C) before conducting the laboratory MIM test.
[0060]
[0063] Measurements of the windshield damping loss factor (η) were performed according to the following procedure: Procedure 1: The windshield is conditioned for at least 4 hours at the test temperature of 20 + / - 1 °C prior to testing. The windshield is suspended on a long (>40 cm) string (e.g., hemp string) at the centre of the rearview mirror base to minimise damping associated with the support. The windshield is excited on the exterior surface by a Brüel & Kjær impulse impact hammer, 400 mm from the top side of the windshield and 400 mm from the side closest to the driver. The panel response to the excitation is acquired by an accelerometer at the same location, but on the inside of the windshield surface. The accelerometer and its leading cable should be as light as possible so as not to distort the windshield vibration response. Knowing the exact excitation force and response, a frequency response function was generated by a Fast Fourier Transform program, as shown in Figure 1. The damping loss factor (η) for the first vibration mode is calculated from the frequency response function by the half-power method: η = Δf / f0 = (f2-f1) / f0.
[0061]
[0064] An example of a response curve is shown in Figure 1. If the response curve is highly asymmetric and f2 cannot be determined, the steeper side of the peak (usually the left side of the peak) can be used and reflected to the right side of the peak. Thus, the damping loss factor (η) is η = Δf / f0 = 2 * It can be calculated as (f0-f1) / f0.
[0062]
[0065] In various embodiments, the interlayers of the present invention have a thickness per windshield area (1 / m2) measured directly on the windshield. 2 ) the windshield attenuation loss factor (η) is at least 0.0450 (0.0500, 0.0550, 0.0600, 0.0650, 0.0700, 0.0750, 0.0800, 0.0850).
[0063]
[0066] For many of the following examples, the damping loss factor (LF), also referred to as the laboratory MIM loss factor, was also measured in the laboratory on small laminate samples (size (1 inch x 12 inches)) by mechanical impedance measurements according to ISO 16940. The laboratory MIM loss factor LF can be correlated to the windshield damping loss factor η. When possible, it is desirable to have the damping loss factor measured and characterized on actual windshields using the procedure described above (Procedure 1) which is more representative of actual windshield applications. However, it may not always be possible or practical to measure a complete windshield, and therefore it is understood that smaller laminated glazing and smaller samples may be measured as described herein.
[0064]
[0067] Mean Break Height (MBH) (impact resistance) was measured at 29.4°C temperature per ANSI / SAE Z26.1-1996. Tests are measured at known thicknesses and, if necessary, normalized to a constant thickness (e.g., 30 mils or 45 mils) so that various interlayers can be compared at the same interlayer thickness. The laminates tested were made with 2.3 mm annealed glass and the interlayers described in the examples below. A 5 pound steel ball was used in the impact test. The mean break height delta shown below is the difference between the respective Example MBH and Comparative Example 1 MBH according to the formula: Mean Break Height Delta (meters) = Example MBH - Comparative Example 1 MBH.
[0065]
[0068] The present invention also includes the following embodiments, which are set forth below.
[0066]
[0069] One embodiment is a laminated glazing comprising: a first glass substrate; a multilayer polymer interlayer; and a second rigid substrate; the multilayer polymer interlayer comprising: a first poly(vinyl acetal) resin having a first residual hydroxyl content and a first residual acetate content, and a first plasticizer, the first poly(vinyl acetal) resin having a glass transition temperature (T g a first layer comprising a second poly(vinyl acetal) resin having a second residual hydroxyl content and a second plasticizer, the second layer having a glass transition temperature (T g a second layer comprising a third poly(vinyl acetal) resin having a third residual hydroxyl content and a third plasticizer, the second layer having a glass transition temperature (T g ), and the second layer is between the first and third layers, and when measured according to procedure 1, the laminated glazing has a thickness of 1 / m2 per glazing area measured directly on the laminated glazing. 2The laminated glazing may be a windshield, for example a windshield for an automobile or other vehicle. The laminated glazing or windshield may be used in head-up display applications in vehicles.
[0067]
[0070] In an embodiment, an interlayer in a laminated glazing or windshield can include an interlayer in which the first poly(vinyl acetal) resin and the third poly(vinyl acetal) resin are the same. In an embodiment, the difference between the first residual hydroxyl content and the second residual hydroxyl content is at least 2.0 (2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0) weight percent.
[0068]
[0071] In an embodiment, the first plasticizer and the third plasticizer are the same. In another embodiment, the second plasticizer is the same as at least one of the first plasticizer or the third plasticizer. In an embodiment, the at least one plasticizer may be a mixture of two or more plasticizers. In an embodiment, the at least one plasticizer may be a high refractive index plasticizer as defined herein.
[0069]
[0072] In an embodiment, the multilayer interlayer is a tapered interlayer, which may have one tapered layer, two tapered layers, three (or more) tapered layers, or all layers may be tapered.
[0070]
[0073] In embodiments, the interlayer has a graduated color band, while in other embodiments the interlayer includes an IR absorber in at least one layer. In embodiments, the interlayer can have a graduated color band and can include an IR absorber in at least one layer.
[0071]
[0074] In an embodiment, the interlayer further comprises at least one non-poly(vinyl acetal) layer. In an embodiment, the interlayer comprises a tie layer between the layers.
[0072]
[0075] In an embodiment, the interlayer has a MIM loss factor (LF) at 20° C. as measured by ISO 16940 of at least 0.29 (0.30, 0.31, 0.32, 0.33, 0.34).
[0073]
[0076] Any of the features described herein can be combined with any other feature. For example, the laminated glazing or windshield can include an interlayer with a non-poly(vinyl acetal) layer and a gradation color band, or the interlayer can include an IR absorber in at least one layer and can be a tapered interlayer, or the interlayer can have a first poly(vinyl acetal) resin and a third poly(vinyl acetal) resin that are the same, and at least the first residual hydroxyl content and the second residual hydroxyl content can be at least 2.0 (2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0) weight percent difference between the first residual hydroxyl content and the second residual hydroxyl content. Other combinations of features are also included and considered. EXAMPLES
[0074]
[0077] Exemplary multilayer interlayers were prepared by blending and melt extruding 100 parts by weight of poly(vinyl butyral) resin with various amounts of plasticizers and other common additives (as described above), as shown in Table 1. For the disclosed examples, a blend of 3GEH plasticizer and DPG dibenzoate plasticizer was used, with the amount (%) of 3GEH in the blend shown in Table 1. The three PVB resins used were:
[0078] PVB1: PVB resin with residual PVOH content of about 18.5% by weight
[0079] PVB2: PVB resin with residual PVOH content of about 9% by weight
[0080] PVB3: PVB resin with residual PVOH content of about 10.5% by weight
[0081] In addition, comparative examples of commercially available acoustic trilayers (Saflex® Q series PVB interlayer from Eastman Chemical Company (Comparative Example 1), and a commercially available competitive standard acoustic PVB sample (Comparative Example 2)) were also used as shown in the table below.
[0075]
[0082] The multi-layer interlayers were then used to construct various laminates and windshields, as shown in the tables and described more fully below.
[0076]
[0083] The improvement in acoustic properties, such as the attenuation loss factor (η), of a windshield can most easily be understood by comparison of laminates containing multi-layer (three-ply) interlayers. As shown and described below, these examples demonstrate the attenuation properties of a windshield when certain modifications are made to the multi-layer interlayer.
[0077]
[0084] For each of the interlayers, the laboratory MIM loss factor (LF) at 20°C was measured. Laboratory MIM loss factor refers to the MIM loss factor tested on laboratory scale specimens (2.54 cm x 30.48 cm (1'' x 12'')) made with 2.3 mm annealed glass instead of a larger laminate such as a complete windshield, as previously described. Impact resistance was also measured on laminates made using the interlayers, as previously described. The results are shown in Table 1 below.
[0078] [Table 1]
[0079]
[0085] Some of the interlayers shown in Table 1 were used in windshield attenuation loss factor (η) testing. The glass thickness and dimensions of the windshields tested are shown in Table 2 below. (Per area of windshield or glazing (1 / m2) measured directly on the windshield)2 The damping loss coefficients (η) of the
[0080] [Table 2]
[0081]
[0086] It was found that there is a correlation between the laboratory MIM loss factor (LF) and the windshield attenuation loss factor (η). Figure 2 shows the windshield attenuation loss factor (η) compared to the laboratory MIM loss factor (LF) for Windshield 2, and Figure 3 shows the windshield attenuation loss factor (η) compared to the laboratory MIM loss factor (LF) for Windshield 1. As shown in Figures 2 and 3, the windshield attenuation loss factor (η) increases as the laboratory MIM loss factor increases.
[0082]
[0087] The correlation between the laboratory MIM loss factor (LF) and the windshield attenuation loss factor (η) can be further depicted in Figure 4. Figure 4 shows the normalized windshield area (1 / m2) compared to the laboratory MIM loss factor (LF) for both windshields. 2 ) Windshield attenuation loss coefficient (η). As shown in Figure 4, the windshield attenuation loss coefficient (η) is calculated per unit area (1 / m 2 ) the windshield attenuation loss factor (η) increases as the laboratory MIM loss factor increases.
[0083]
[0088] There are multiple ways to affect or change the MIM loss factor (and thereby affect or change the windshield attenuation loss factor (η)). For example, the MIM loss factor can be increased by increasing the core layer thickness. For example, comparing Interlayer 3D, Interlayer 3B, Interlayer 3A, and Interlayer 3C, the MIM loss factor increases as the core layer thickness increases. Also, comparing Interlayer 2A, Interlayer 2B, Interlayer 2C, and Interlayer 1A, Interlayer 1B, Interlayer 1C shows that the MIM loss factor increases as the core layer thickness increases.
[0084]
[0089] The MIM loss factor can also be increased by changing the type of plasticizer and the core resin. Comparing interlayer 3D with Comparative Example 1 shows that by using a mixture of two plasticizers (3GEH and DPG-dibenzoate) and by changing the resin used in the core (PVB3 to PVB2), the MIM loss factor increases from 0.284 to 0.302.
[0085]
[0090] Increasing the amount of plasticizer in the skin layers also improves the MIM loss factor. Comparing Interlayer 4A, Interlayer 2A, and Interlayer 1A to Interlayer 4B, Interlayer 2B, and Interlayer 1B shows that as the plasticizer level in the outer (skin) layers increases, the MIM loss factor increases.
[0086]
[0091] In some cases, as shown in Examples 4A, 4B, and 4C, the lab MIM LF does not always increase with core layer thickness, and it appears that there is an optimal core layer thickness in the multilayer that can result in the maximum lab MIM LF at a given skin plasticizer level.
[0087]
[0092] In some cases, the lab MIM LF does not always increase with the amount of plasticizer in the skin layers, as shown in Interlayer Example 1C, Interlayer Example 2C, and Interlayer Example 4C. It is also clear that there is an optimal plasticizer level in the skin layers in a multilayer that can result in the maximum lab MIM LF at a given core thickness.
[0088]
[0093] Impact resistance decreases with increasing core layer thickness, as shown by comparing Example 4A, Example 4B, and Example 4C, by comparing Example 2A, Example 2B, and Example 2C, and by comparing Example 1A, Example 1B, and Example 1C. By comparing Sample 1A, Sample 1B, and Sample 1C, which has better impact and less plasticizer, with Sample 2A, Sample 2B, and Sample 2C, and by comparing Sample 2A, Sample 2B, and Sample 2C with Sample 4A, Sample 4B, and Sample 4C, it is possible to reduce the loss of impact resistance due to increasing core layer thickness by reducing the skin plasticizer loading.
[0089]
[0094] In conclusion, laminated glazing, such as automobile windshields, including a multilayer interlayer according to the present invention has enhanced attenuation compared to other laminated glazing. Other advantages will be readily apparent to those skilled in the art.
[0090]
[0095] Although the present invention has been disclosed in conjunction with a description of certain specific embodiments, including what are currently considered to be preferred embodiments, the detailed description is intended to be illustrative and should not be understood as limiting the scope of the disclosure. As will be understood by those skilled in the art, embodiments other than those described herein are encompassed by the present invention. Modifications and variations of the described embodiments may be made without departing from the spirit and scope of the present invention.
[0091]
[0096] It is further understood that any of the ranges, values or characteristics given for any one component of this disclosure may be used interchangeably with any of the ranges, values or characteristics given for any other component of this disclosure to form an embodiment with the respective given values of the components given throughout this specification.For example, an interlayer film may be formed that includes any of the plasticizers given, and has any of the residual hydroxyl contents given, in addition to including any of the plasticizers given, to form many permutations that are cumbersome to list but are within the scope of this disclosure.Furthermore, unless otherwise indicated, the ranges given for a class or category, such as phthalates or benzoates, may also apply to species within the class or category members, such as dioctyl terephthalate.
Claims
1. a first rigid substrate; A multilayer polymer interlayer; and a second rigid substrate; A laminated glazing comprising: The multilayer polymer interlayer film comprises: A first poly(vinyl acetal) resin having a first residual hydroxyl content and a first residual acetate content, and a first plasticizer, the first poly(vinyl acetal) resin having a glass transition temperature (T g a first layer having a a second poly(vinyl acetal) resin having a second residual hydroxyl content and a second plasticizer, the second poly(vinyl acetal) resin having a glass transition temperature (T g a second layer having a A third poly(vinyl acetal) resin having a third residual hydroxyl content and a third plasticizer, the third poly(vinyl acetal) resin having a glass transition temperature (T g A third layer having Including, the second layer is between the first layer and the third layer; When measured according to Procedure 1, the laminated glazing has a glazing area (1 / m2) per glazing area measured directly on the laminated glazing. 2 ) a damping loss coefficient (η) of at least 0.0450.
2. 2. The laminated glazing of claim 1, wherein the first poly(vinyl acetal) resin and the third poly(vinyl acetal) resin are the same.
3. 2. The laminated glazing of claim 1, wherein the difference between the first residual hydroxyl content and the second residual hydroxyl content is at least 2.0 weight percent.
4. 2. The laminated glazing of claim 1, wherein the multi-layer interlayer is a tapered interlayer.
5. 10. The laminated glazing of claim 1, wherein one layer of the multilayer interlayer has a tapered profile.
6. 10. The laminated glazing of claim 1, wherein the interlayer has a gradient color band.
7. 10. The laminated glazing of claim 1, wherein the interlayer comprises an IR absorber in at least one layer.
8. 10. The laminated glazing of claim 1, wherein the interlayer further comprises a non-poly(vinyl acetal) layer.
9. 2. The laminated glazing of claim 1, wherein the interlayer has a MIM loss factor (LF) at 20° C. measured by ISO 16940 of at least 0.
29.
10. 10. The laminated glazing of claim 1, wherein the laminated glazing is a vehicle sidelight, sunroof or other window.
11. A first glass substrate; A multilayer polymer interlayer; and a second rigid substrate; A windshield comprising: The multilayer polymer interlayer film comprises: A first poly(vinyl acetal) resin having a first residual hydroxyl content and a first residual acetate content, and a first plasticizer, the first poly(vinyl acetal) resin having a glass transition temperature (T g a first layer having a a second poly(vinyl acetal) resin having a second residual hydroxyl content and a second plasticizer, the second poly(vinyl acetal) resin having a glass transition temperature (T g a second layer having a A third poly(vinyl acetal) resin having a third residual hydroxyl content and a third plasticizer, the third poly(vinyl acetal) resin having a glass transition temperature (T g A third layer Including, the second layer is between the first layer and the third layer; When measured according to Procedure 1, the windshield has a windshield area (1 / m2) measured directly on the windshield. 2 ) has a damping loss factor (η) of at least 0.0450.
12. 12. The windshield of claim 11, wherein the first poly(vinyl acetal) resin and the third poly(vinyl acetal) resin are the same.
13. 12. The windshield of claim 11, wherein a difference between the first residual hydroxyl content and the second residual hydroxyl content is at least 2.0 weight percent.
14. 12. The windshield of claim 11, wherein the multilayer interlayer is a tapered interlayer.
15. 12. The windshield of claim 11, wherein one layer of the multilayer interlayer has a tapered profile.
16. 12. The windshield of claim 11, wherein the interlayer has a gradient color band.
17. 12. The windshield of claim 11, wherein the interlayer comprises an IR absorber in at least one layer.
18. 12. The windshield of claim 11, wherein the interlayer further comprises a non-poly(vinyl acetal) layer.
19. 12. The windshield of claim 11, wherein the interlayer has a MIM loss factor (LF) at 20° C. measured by ISO 16940 of at least 0.
29.
20. 12. The windshield of claim 11 for use in a head-up display application in a vehicle.